Błędy w użyciu przyimków polskich - Stanka Bonowa Dojczynowa (Postscriptum Polonistyczne)
The article describes some main problems that Bulgarian students meet during their study of Polish language. The main mistakes in usage of Polish prepositions are grouped in several typological categories and the possible reasons for those mistakes are briefly described. The article is based on a corpus of mistakes made by students that study Polish at the University of Veliko Turnovo. The analysis allows to classify the main difficulties in acquiring Polish prepositions and to build conscious strategy that allows avoiding them in the process of teaching Polish language.